Analisis Praktik Pemasaran Digital dan Isu Privasi Data: Strategi Etika Bisnis untuk Meningkatkan Kepercayaan Pengguna - Nadia Wangsa Kusumadiningrat; Halimah Zahrah; Sadam Maulana; Dendi Nur Fadilah (Teewan Journal Solutions, 2025)
This research aims to analyze business ethics strategies in the context of digital marketing that involves the use of consumer personal data. Digital marketing practices have a high potential to cause privacy violations, which can undermine public trust. The Cambridge Analytica case study serves as a real example of the negative impact of unethical marketing. This research employs descriptive qualitative methods with a literature review and case study approach. The analysis is conducted using content analysis to identify relevant themes and ethical strategies. The research findings indicate that the implementation of transparency, data protection, and open communication are key strategies in rebuilding user trust.